Análisis de los medios tradicionales en los entornos virtuales caso Diario La Hora cantón Quevedo año 2021 - Ramirez Casillas, Grace Lizbeth (2021)
This research project was carried out through a digital questionnaire addressed to the inhabitants of the “Viva Alfaro” sector, belonging to the Quevedo canton. Its purpose is to determine the impact of Traditional Media in virtual environments, because, with the advancement of technology, these media have had to be digitized. Currently most people, especially young people, prefer and use websites for a number of activities, one of them is to stay informed of events that have occurred at the national and international level. One of the results obtained in this research was that the majority of the inhabitants of the “Viva Alfaro” sector remain connected on the websites for between four and six hours a day, with Facebook being the most used social network.